THE INFLUENCE OF GOLD PRICE FLUCTUATIONS, FEAR OF MISSING OUT (FOMO), AND INVESTMENT KNOWLEDGE ON CUSTOMER INTEREST IN THE GOLD INSTALLMENT PRODUCT AT BANK SYARIAH INDONESIA - Nanda Chairani; Nurjanah; Zefri Maulana (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2026)
Gold is regarded as a stable investment instrument and a haven asset amid economic uncertainty. In line with advancements in digital financial services and the growing preference for Sharia-compliant financial products, Bank Syariah Indonesia (BSI) introduced its Gold Instalment Program as a practical, Sharia-compliant financing facility for gold ownership. However, public interest, particularly among BSI KC Langsa customers, is relatively low. This study examines the effects of Gold Price Fluctuations, Fear of Missing Out (FOMO), and Investment Knowledge on Customer Interest in the BSI Gold Instalment Program. The research was conducted at BSI KC Langsa using a quantitative method and a non-probability convenience sampling technique. A total of 100 respondents were selected using the Slovin formula. The findings indicate that, to some extent, Gold Price Fluctuations significantly influence Customer Interest, whereas FOMO and Investment Knowledge do not. Simultaneously, all three variables significantly influence Customer Interest. This study is expected to provide insights for the public in making investment decisions and for BSI in developing more effective educational and promotional strategies.